2008
DOI: 10.1002/kin.20356
|View full text |Cite
|
Sign up to set email alerts
|

On the photoreactivity of vitamin K compounds

Abstract: Rate constants for conversion of vitamin K 1 -and K 2 -derived 1,3-quinone methides into 1,2-quinone methides have been measured in CH 3 CN solutions in the presence of Brönsted acids and bases. Second-order rate constants approach the diffusion-controlled limit and are essentially independent of the (acid or base) strength of the catalyst. On the other hand, rate constants for triplet quenching of 2-methyl-3-undecyl-1,4-naphthoquinone, used as model compound, are presented and compared with data for 1,4-napht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…RF and CBBP have several analogies with known CDOM components, , while the 1NN triplet state is less reactive than that of AQ2S and it is very conveniently studied by laser flash photolysis. , Indeed, the study of the reactivity of 3 1NN*, 3 RF*, and 3 CBBP* with PRP required the use of a laser apparatus, which was also used to measure again the second-order reaction rate constant between PRP and 3 AQ2S*. It has been reported that the measured laser and steady-irradiation 3 AQ2S* second-order rate constants are very similar in the case of nitrobenzene, , but the laser apparatus might also detect physical quenching phenomena that do not lead to chemical reactions and are not taken into account by steady irradiation . Moreover, in some cases the initial substrate is reformed during steady irradiation by a combination of oxidation and reduction processes. , The experimental laser flash photolysis data obtained in this work are summarized in Figure S10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RF and CBBP have several analogies with known CDOM components, , while the 1NN triplet state is less reactive than that of AQ2S and it is very conveniently studied by laser flash photolysis. , Indeed, the study of the reactivity of 3 1NN*, 3 RF*, and 3 CBBP* with PRP required the use of a laser apparatus, which was also used to measure again the second-order reaction rate constant between PRP and 3 AQ2S*. It has been reported that the measured laser and steady-irradiation 3 AQ2S* second-order rate constants are very similar in the case of nitrobenzene, , but the laser apparatus might also detect physical quenching phenomena that do not lead to chemical reactions and are not taken into account by steady irradiation . Moreover, in some cases the initial substrate is reformed during steady irradiation by a combination of oxidation and reduction processes. , The experimental laser flash photolysis data obtained in this work are summarized in Figure S10.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the measured laser and steady-irradiation 3 AQ2S* second-order rate constants are very similar in the case of nitrobenzene, 59,60 but the laser apparatus might also detect physical quenching phenomena that do not lead to chemical reactions and are not taken into account by steady irradiation. 61 Moreover, in some cases the initial substrate is reformed during steady irradiation by a combination of oxidation and reduction processes. 62,63 The experimental laser flash photolysis data obtained in this work are summarized in Figure S10.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[67][68][69] A partir dos trabalhos pioneiros de Porter, vários estudos com fotólise por pulso e isolamento cromatográfico permitiram a identificação de intermediários e de produtos decorrentes de reações fotoquímicas de Fotoisomerização de filoquinona em pentano degasado. 70,71 Há mais de 60 anos, em um trabalho sobre "β-oxidação da cadeia lateral de hidróxi-naftoquinonas", Ettlinger menciona que lapachol (encontrado na madeira do ipê, 72,73 A fotoquímica do lapachol voltou a ser estudada recentemente por Gorner: 60 o rendimento quântico de formação de 1 O 2 é desprezível; foi detectada a presença, por fotólise por pulso de laser, do intermediário 1,3-QM, que evolui a 1,2-QM e, daí, a produtos propostos -pois um único produto encontrado por c.l.a.e. (cromatografia líquida de alta eficiência) não teve sua estrutura "identificada ou investigada" Apesar da reação ocorrer a partir do estado excitado singlete e triplete de cetonas, a regio-e estereoseletividade da reação dependem da multiplicidade do estado excitado.…”
Section: Figura 17 Fotoquímica De Derivados Da Lausonaunclassified
“…For natural compounds, photochemical-induced formation of an o -QM intermediate was also reported for 2-isoprenyl-3-methyl-1,4-naphthoquinones, such as vitamin K derivatives . For example, the photoredox reaction of menaquinone 1 (vitamin K2) or phylloquinone (vitamin K1) leads, after 1,4-proton transfer, to a zwitterionic species that tautomerizes to a metastable isomeric o -QM.…”
Section: Introductionmentioning
confidence: 99%